Low-pass filteration using adaptive delta modulation - Rajs, Arkadiusz; Maszewski, Mirosław (Journal of Education, Health and Sport, 2017)
Linear Delta Modulation (DM) is applicable to processing of signals in digital systems of telecommunication. One of most interesting kind of LDM is Adaptative DM (ADM). This Work presents method of using ADM for low-pass digital filtration.